Circadian Blood Pressure Variation in Normotensive Patients With Panic Disorder. (September 2014) - Alici, Hayri; Ercan, Suleyman; Bulbul, Feridun; Alici, Demet; Alpak, Gokay; Davutoglu, Vedat
Nondipper pattern of blood pressure (BP) is associated with cardiovascular risk. In this study, we compared dipper versus nondipper patterns between normotensive patients with panic disorder (PD) and a control group. A total of 25 normotensive patients with PD and 25 controls were enrolled. Twenty-four-hour ambulatory BP monitoring was performed in all patients. At least 10% of sleep-related nocturnal decrease in systolic and diastolic BP was accepted as dipper status, while decreases <10% were defined as a nondipper. Patients with PD had significantly higher incidence of nondipper BP pattern than controls. The reduction of nighttime BP in both systolic and diastolic and mean BP was significantly lower in patients with PD than in the control group (7.6% ± 4.3% vs 13% ± 3.9%, P < .001; 11% ± 7% vs 15% ± 5%, P = .004; 9% ± 5% vs 14% ± 4%, P = .002, respectively). Panic disorder is associated with nondipper BP pattern, causing impaired circadian BP in normotensive settings.